APPLICATION OF DATA MINING TO DETERMINE THE LEVEL OF FISH SALES IN PT. TRANS RETAIL WITH FP-GROWTH METHOD - Tamba, Saut Parsaoran; Sitanggang, Mario; Situmorang, Bimo Christhoper; Panjaitan, Gracia Laura; Marlince Nababan (INFOKUM, 2022)
Trans Retail Indonesia is one of the shopping places in the city of Medan. Trans Retail Indonesia is engaged in providing raw materials such as selling fish. However, at Trans Retail Indonesia, sales data collection still uses a manual system, so this store has not been able to determine which type of fish has the highest level of sales. So this affects the availability of goods and results in a lack of stock in this store. So we need a data mining system with the FP-Grwoth method to analyze fish sales data so that the results of the analysis become a reference for stores in determining the supply of fish stocks. The results of the analysis carried out by researchers from the data obtained are the fish that is most in demand is the Jengka Split with a value of 90%, and if you take a split Jengka fish, you will take anchovy buntiaw with a value of 54%. If you take an anchovy, it will take a large anchovy and will take a white Peda fish with a value of 100%.